ANALISIS LITERATUR KONSEP SEL DALAM PEMBELAJARAN SAINS: STRATEGI, TANTANGAN, DAN SOLUSI - Laili Lutfianah; Nabila Wanda Yusela; Shela Permatasari; Afridha Laily Alindra (STKIP Subang, 2026)
The concept of cells is a fundamental topic in science learning that discusses the structure, function, and role of cells as the smallest units of living organisms. However, cell concepts are often considered difficult to understand because they are abstract and complex. This study aims to analyze cell concepts in science learning, the teaching strategies used, as well as the challenges and solutions in the learning process. The method used in this study is a qualitative Systematic Literature Review (SLR) through the analysis of various relevant scientific articles and literature. The results of the review indicate that learning strategies such as Project Based Learning (PjBL), inquiry-based learning, visual media, animated videos, virtual laboratory activities, and interactive e modules can improve students’ understanding of cell concepts and their active involvement in learning. Nevertheless, the teaching of cell concepts still faces several challenges, including limited facilities, low student representation skills, and the lack of innovative learning media. Therefore, the use of digital technology and the implementation of active learning models are needed to make cell concept learning more effective, engaging, and meaningful for students.